Era-like GTP protein gene expression in rice - X. Zhou; K. Shafique; M. Sajid; Q. Ali; E. Khalili; M. A. Javed; M. S. Haider; G. Zhou; G. Zhu (Brazilian Journal of Biology, 2021)
Abstract The mutations are genetic changes in the genome sequences and have a significant role in biotechnology, genetics, and molecular biology even to find out the genome sequences of a cell DNA along with the viral RNA sequencing. The mutations are the alterations in DNA that may be natural or spontaneous and induced due to biochemical reactions or radiations which damage cell DNA. There is another cause of mutations which is known as transposons or jumping genes which can change their position in the genome during meiosis or DNA replication. The transposable elements can induce by self in the genome due to cellular and molecular mechanisms including hypermutation which caused the localization of transposable elements to move within the genome. The use of induced mutations for studying the mutagenesis in crop plants is very common as well as a promising method for screening crop plants with new and enhanced traits for the improvement of yield and production. The utilization of insertional mutations through transposons or jumping genes usually generates stable mutant alleles which are mostly tagged for the presence or absence of jumping genes or transposable elements. The transposable elements may be used for the identification of mutated genes in crop plants and even for the stable insertion of transposable elements in mutated crop plants. The guanine nucleotide-binding (GTP) proteins have an important role in inducing tolerance in rice plants to combat abiotic stress conditions.